Analyzing ISP's Industry Of Pakistan - Imtiaz, Ghaffar (2002)
In Pakistan, ISPs started to provide services in 1996. Today, the ISp market in Pakistan is booming, and new ISPs are being set up at a regular interval. Currently, the ISP market in Pakistan has a large number, 122 licensees. This show there is an increasing trend in the Internet market business and numbers of ISPs are increasing over the years.